2018
DOI: 10.1016/j.jaip.2017.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Impact and Unmet Needs of Nonadherence in Asthma and Chronic Obstructive Pulmonary Disease: Where Do We Go From Here?

Abstract: Nonadherence to treatment, and its associated health and economic burden, is particularly problematic in asthma and chronic obstructive pulmonary disease management because of heterogeneous patient populations and the need for an inhaled route of drug administration. Symptom variability, comorbidities, and device switching further add to suboptimal adherence rates. As opposed to controlled clinical trials, real-life studies show consistently low inhaler adherence in daily practice, yet exact adherence rates ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 57 publications
2
64
0
Order By: Relevance
“…Classic randomized control trials investigating the efficacy of inhaler devices tend to enrol very selective groups of patients . In real‐life practice setting, factors such as imperfect inhalation techniques and non‐adherence to treatment are common, negatively impacting inhaler treatment outcomes . The current study indicated that within Korean real‐life practice setting, pMDI was comparable to DPI in preventing asthma exacerbations, and led to better asthma control, despite the potential for imperfect adherence and inhaler technique.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Classic randomized control trials investigating the efficacy of inhaler devices tend to enrol very selective groups of patients . In real‐life practice setting, factors such as imperfect inhalation techniques and non‐adherence to treatment are common, negatively impacting inhaler treatment outcomes . The current study indicated that within Korean real‐life practice setting, pMDI was comparable to DPI in preventing asthma exacerbations, and led to better asthma control, despite the potential for imperfect adherence and inhaler technique.…”
Section: Discussionmentioning
confidence: 79%
“…11,17,18 In real-life practice setting, factors such as imperfect inhalation techniques and non-adherence to treatment are common, [18][19][20][21][22] × strength Categorized as 0, >0 to ≤250, >250 to ≤500, >500 μg daily ICS dosage (low, medium and high as per GINA guidelines) Oral thrush Diagnostic code for oral thrush OR Prescription of antifungal therapy negatively impacting inhaler treatment outcomes. 17,[22][23][24][25] The current study indicated that within Korean real-life practice setting, pMDI was comparable to DPI in preventing asthma exacerbations, and led to better asthma control, despite the potential for imperfect adherence and inhaler technique. In addition, while this study was retrospective in nature, data were collected prospectively and thus the patients were not influenced by recall bias.…”
Section: Discussionmentioning
confidence: 99%
“…Also, improving adherence seems to be related to decreased exacerbation risk that may be independent of inhaler technique performance . Adherence may also be an important aspect to consider in terms of cost estimation because it also affects medication costs . Here, medication costs were not considered as a subset, although cost estimations included them in the main source.…”
Section: Discussionmentioning
confidence: 99%
“…3,41,42 Adherence may also be an important aspect to consider in terms of cost estimation because it also affects medication costs. 43 Here, medication costs were not considered as a subset, although cost estimations included them in the main source. Medication costs may decrease due to better inhaler technique because as clinical control improves, other concurrent therapies are needed less often (such as oral corticosteroids or antibiotics), and the optimal inhaled dosing may also be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…This can partly be explained by two key challenges facing healthcare professionals and caregivers. These are incorrect inhaler use [16] and poor patient adherence to treatment [17]. The former can be addressed by appropriate and consistent training by the healthcare professionals.…”
Section: What Are the Current Incentives Driving Inhaler Development mentioning
confidence: 99%